Experiences, challenges and acceptance of e-learning by adult learners in sandwich programme of Nnamdi Azikiwe University Awka, Nigeria - Obiageli Chinyelu Chukwuemerie; Eunice Akpan; Perpetua Ukamaka Okoye (S&Co Publishing, 2024)
This study investigated the experiences, challenges and acceptance of e-learning by adult learners in the Sandwich programme of Nnamdi Azikiwe University, Awka. Descriptive survey research design was adopted. The population of study comprised all 381 adult learners offering Sandwich Programmes in the 2021/2022 Session in the Faculty of Education, Nnamdi Azikiwe University, Awka was also the sample size. Three research questions guided the study. Data for the study were collected by means of a validated structured questionnaire titled “Questionnaire on E-Learning by Adult Learners” (QEAL) designed in google form format. Cronbach’s Alpha values of 0.89, 0.78 and 0.89 for clusters I – III were obtained after testing for reliability. Mean and standard deviation were used to analyze data. The findings revealed that adult learners had pleasant experiences of e-learning in sandwich programmes of Nnamdi Azikiwe University in the 2021/2022 Session; and faced some challenges that included unstable internet connectivity, technical problems during online classes and difficulties associated with practical courses in distance learning. Nevertheless, adult learners highly accepted e-learning after their exposure to a higher level of e-learning in the 2021/2022 academic session by the Sandwich programme in Nnamdi Azikiwe University, Awka. It was recommended amongst others that the management of Nnamdi Azikiwe University should invest more in e-learning by way of upgrading their ICT architecture and organize more trainings on adaptation to e-learning for their adult learners that are still lagging behind and for fuller and more profitable utilization of the innovations in the Qverse learning management system.